Japan and the South China Sea - Noraini bt Zulkifli; Vivian Louise Forbes (Andalas Journal of International Studies (AJIS), 2016)
This article examines and analyses Japan’s current interest in theSouth China Sea, by first alluding to the historical context of that country’s involvement from the mid-1930s to the end of the Pacific War, 1945. It then outlines Japan’s energy security needs and that country’s national policy relating to securing safety for its flagged ships and those vessels assisting in promoting Japan’s export and import and the diplomatic role that Japan plays towards regional stability. Japan in their Diplomatic Bluebook stated that the priority for Japan is to guarantee the securityandprosperity of the countryand its people. Here,it is clear thatthe Japanese Government will trytodo everything togive the besttoensure their survival. Japan’s interest in South China Sea is because it is deemed critical for the Japanese security.Keywords: Japan, Energy, Maritime Security, Military, South China Sea